Crime, culture and collecting: the illicit cycad market in South Africa - Torgersen, Jonas Sørflaten (2017)
It is widely accepted that illicit markets are driven by specific contextual factors that determine their nature and scope. Two points in particular have not been explored in the literature on wildlife crime. First, while illicit markets around commodities such as drugs and weapons are fuelled by consumers arguably in need of, or addicted to, the product, the desires of buyers that shape wildlife markets are often shaped by cultural norms which may seem irrational to outsiders. Second, given that wildlife markets are seldom as stringently regulated as those in respect of drugs, weapons or other commodities, the nature of the criminal enterprises that source, move and sell the products are possibly very different. The study examines these two factors – the culture of markets and the degree of criminal enterprise or organisation within them – through a case study of a largely unexamined environmental crime market in South Africa, that of rare cycad plants. Cycads are widely exploited, moved and sold in the country by a network of increasingly criminalised operations. State action against these markets is not a priority and has had only few successes in limiting the trade of an increasingly scarce plant. A detailed examination of the market and its consumers suggests that it is strongly shaped by a particular South African culture which draws on (often mythical) connections to the land, including its fauna and flora. Ironically, those active in the market argue that their objective for doing so is conservation, even if illicit collections are the prime threat to the species. Although the academic and conservation community have attempted to develop and implement conservation tools and strategies, limited law enforcement and regulatory mechanisms have produced a flexible illicit market where a set of intermediaries play the key role. While the market shows signs of internal competition, it operates relatively openly, and does not display the levels of violence of other criminal markets in similar stages of development